"Calidad en el Cuidado de Enfermería Según la Perspectiva de los Padres y/o Cuidadores de Niños Hospitalizados" - Teran Lozada, Lourdes Maritza (2014)
The present investigation of quantitative - descriptive type I realize with the aim to determine the Quality in the Attention in the Care of Infirmary according to the perspective of the parents and / or keepers of the children hospitalized in the service of Pediatrics of the Regional Educational Hospital of Trujillo. The sample population was constituted by 200 parents and / or keepers which were assembling the criteria of selection, I apply a survey to them, where the information was gathered and were processed following a poll and statistical of manual tabulation, the obtained results were that 85 % of the parents and / or keepers of hospitalized children receive a good quality of attention of infirmary, whereas 2 per cent they receive a quality of regular attention and 13 per cent they receive a quality of low attention. Keywords: Quality of care and nursing care.